PresentationTrainer: Oral Presentation Support System for Impression-Related Feedback - Yi, Shengzhou; Yumoto, Hiroshi; Wang, Xueting; Yamasaki, Toshihiko (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
In order to support the pratice of oral presentation, we developed PresentationTrainer which includes (1) a presentation impression prediction system and (2) a presentation slide analysis system. For the presentation impression prediction system, we proposed two methods, using Support Vector Machine and Markov Random Field, or using multimodal neural network, to predict audiences’ impressions for speech videos. For the slide analysis system, we used Convolutional Neural Network and Global Average Pooling to evaluate the design of slides. We then used Class Activation Mapping to provide visual feedback for showing which areas should be modified.